A review of Ghana's energy sector national energy statistics and policy framework. Issue 1 (31st December 2016) - Asumadu-Sarkodie, Samuel; Owusu, Phebe Asantewaa
Abstract: In this study, a review of Ghana's energy sector national energy statistics and policy framework is done to create awareness of the strategic planning and energy policies of Ghana's energy sector that will serve as an informative tool for both local and foreign investors, help in national decision-making for the efficient development and utilization of energy resources. The review of Ghana's energy sector policy is to answer the question, what has been done so far? And what is the way forward? The future research in Ghana cannot progress without consulting the past. In order to ensure access to affordable, reliable, sustainable, and modern energy for all, Ghana has begun expanding her economy with the growing Ghanaian population as a way to meet the SDG (1), which seeks to end poverty and improve well-being. There are a number of intervention strategies by Ghana's Energy sector which provides new, high-quality, and cost-competitive energy services to poor people and communities, thus alleviating poverty. Ghana's Energy sector has initiated the National Electrification Scheme, a Self-Help Electrification Program, a National Off-grid Rural Electrification Program, and a Renewable Energy Development Program (REDP). The REDP aims to: assess the availability of renewable energy resources, examine the technical feasibility and cost-effectiveness of promising renewable energy technologies, ensure the efficient production and use of the Ghana's renewable energy resources, and develop an information base that facilitates the establishment of a planning framework for the rational development and the use of the Ghana's renewable energy resources.